Pinnaspis strachani (Cooley) (Hemiptera: Diaspididae) infesting neem trees (Azadirachta indica A. Juss., Meliaceae) in Bahia, Brazil - de Castro, Marcelo Tavares; Montalvão, Sandro Coelho Linhares; Wolff, Vera Regina dos Santos (EntomoBrasilis, 2020)
Pinnaspis strachani (Cooley) (Hemiptera: Diaspididae), a highly polyphagous scale insect and a known pest of various crops, is reported for the first time infesting neem (Azadirachta indica A. Juss., Meliaceae) in Brazil. Infestations of this diaspidid were observed on the trunks, branches, and leaves of neem trees in Barreiras, Bahia, Brazil.